Supplementation With Zinc Proteinate Increases the Growth Performance by Reducing the Incidence of Diarrhea and Improving the Immune Function of Dairy Calves During the First Month of Life - Wo, Yeqianli; Jin, Yuhang; Gao, Duo; Ma, Fengtao; Ma, Zhu; Liu, Zhuo; Chu, Kangkang; Sun, Peng (Frontiers in Veterinary Science, 2022)
Two experiments were conducted to identify the optimal dose of zinc proteinate (ZP) in the diet for dairy calves and then to compare early supplementation with the ZP or zinc methionine (ZM) on the growth performance, incidence of diarrhea, antioxidant status, and immune function of dairy calves during their first month of life. In Experiment 1, forty newborn female Holstein dairy calves were randomly divided into four groups (n = 10): a control group (without ZP supplementation, ZP0) or groups that received ZP supplementation at 40, 80, and 120 mg zinc/d, respectively (ZP40, ZP80, and ZP120). The experiment lasted 14 days, and the growth performance, incidence of diarrhea and serum zinc concentration were analyzed. In Experiment 2, thirty-six newborn female Holstein dairy calves were randomly allocated to three groups (n = 12): a negative control group (without zinc supplementation, CON), a positive control group (supplemented with 80 mg zinc/d in the form of zinc methionine, ZM), and a ZP group (supplemented with 80 mg zinc/d in the form of ZP). The experiment lasted 28 days, and the growth performance, incidence of diarrhea, serum zinc concentration, serum antioxidant indicators, and concentrations of plasma immunoglobulins and cytokines were determined on days 14 and 28. Results showed that in Experiment 1, supplementation with ZP to yield 80 mg zinc/d increased the ADG (P < 0.01) and serum zinc concentration (P < 0.01), and decreased the F/G (P < 0.01) and the incidence of diarrhea (P < 0.05) during days 1-14. In Experiment 2, compared with the CON group, ZP increased the ADG (P < 0.01), ADFI (P < 0.01), serum zinc concentration (P < 0.01), and plasma immunoglobulin G (IgG) (P < 0.01) and IgM (P < 0.01) concentrations, but reduced the incidence of diarrhea (P < 0.01), serum malondialdehyde (P < 0.01) and plasma interleukin-1β (P < 0.01) concentrations during days 1-28. Overall, ZP supplementation to yield 80 mg zinc/d improves the growth performance and immune function, and decrease the incidence of diarrhea of dairy calves, which was comparable to the same dose of zinc in the form of ZM.